Drawing and Ethnography Workshop - Ramos, M. (Decolonizing the Academy, Centre of African Studies, Edinburgh, 21-22 April, 2016, 2016)
Drawing is being revived as an apt tool for fieldwork research in the social sciences but its characteristics and potentialities tend to be frequently misunderstood. The aim of this workshop is to consider the practice of drawing both as a method of research and as a way to present its results. The workshop will focus both theoretically and practically on drawing as a practice, and as a way of thinking and knowing in the field. The participants will be introduced to studies that dwell on drawing in fieldwork and will also be invited to practically experience this relation themselves, in a brief observation and sketching exercise around the Conference grounds. The workshop ends with a final gathering for sharing and discussing the practical observation and sketching experience.